Weakly compatible maps in fuzzy metric spaces - Rangamma, M; Reddy, G Mallikarjun; Rao, P Srikant (Kathmandu University Journal of Science Engineering and Technology, 2011)
In this paper, we prove common fixed point theorems for six self maps by using weakly compatibility, without appeal to continuity in fuzzy metric space. Our results extend, generalized several fixed point theorems on metric and fuzzy metric spaces.